Effects of single-shot and twin-shot shockwaves on urinary enzyme concentrations - (:unkn) unknown (MARY ANN LIEBERT INC PUBL, 1999)
Background and Objective: Extracorporeal shockwave lithotripsy (SWL) remains the first-line treatment of urinary calculi, However, a number of studies have shown that adverse effects on the kidneys and the surrounding tissues may be encountered in short- and long-term follow-up. The aim of this study was to compare the effects of single-shot and twin-shot SWL techniques to identify the safest modality in terms of urinary enzyme excretion. Patients and Methods: In this prospective, investigator-blinded, randomized study, urinary enzymes, beta(2)-microglobulin, microalbumin, Na, K, Ca, and creatinine concentrations were analyzed in 59 consecutive patients. Measurements were performed in urine specimens collected immediately before and after the SWL procedure and also on the 3(rd) and 7(th) days after treatment, which was performed on a Dornier MFL-5000 lithotripter utilizing the twin-shot technique (Group 1; N = 30) or the single-shot technique (Group 2; N = 29) with 3000 shockwaves at 18 kV per treatment. Results: Although there was no statistically significant difference in the results between the groups, urinary levels of microalbumin, alanine and aspartate aminotransferases, beta-2-microalbumin, gamma-glutamyltranspeptidase, Na, K, and Ca rose acutely after SWL, reaching maximum levels on the 3rd day, and returned to the baseline by the 7th day following the treatment in both groups. Conclusion: This study demonstrates that SWL performed by either a single-shot or twin-shot shockwave technique has a transient detrimental effect on renal function, as assessed by urine enzyme concentrations. It is recommended that the twin-shot shockwave technique be used in routine lithotripsy in consideration of the cost-effectiveness provided by the shorter treatment time.
Keywords: WAVE LITHOTRIPSY ESWL; RENAL-FUNCTION; KIDNEY-STONES; DAMAGE; EXPOSURE